Discrete-time constrained control of the fuel cell association with buck-boost dc-dc power converter with continuous input. Issue 12 (2022) - Gaouzi, K.; Fadil, H. El; Benzouina, O.; Idrissi, Z. El; Rachid, A.; Giri, F.
Abstract: This paper proposes a buck-boost converter topology with continuous input-current capability for proton exchange fuel cells (PEMFC) systems. We are considering the problem of controlling systems including, in cascade, two dynamic linear subsystems and two static nonlinear elements of the saturation type. The cascade control strategy is consisting of two main control loops: an inner loop (or current loop) and an outer loop (or voltage loop). It is shown, by a theoretical analysis, that the proposed cascade controller stabilizes the resulting closed-loop system and ensures perfect tracking of step-like output reference signals that are compatible with the system saturating elements. The effectiveness of the proposed cascade controller approach is verified by simulation using MATLAB / Simulink.